An Introduction to Social Sustainability & Interior Architecture - Beeck, Sarah; Smith, Dianne; Lommerse, Marina; Metcalfe, Priya (Paper and Pencil, 2011)
Environments people inhabit and experience have the power to enhance the wellbeing of individuals and their communities. In this unique collection of writing, Life from the Inside: Perspectives on Social Sustainability and Interior Architecture shares new ways of thinking about interior architecture by reconsidering theories, processes and outcomes that relate to how people live now and in the future. The issues raised by the authors are relevant for individuals, government and non-government organisations, professionals, students and communities